Critical Problems in Developing Databases for Upland Areas: the Potential Value of GIS Techniques - Coombes, Mike; Saunders, Caroline; Raybould, Simon (Journal of environmental management, 1993)
There are increasingly complex patterns of policy boundaries which identify those upland and other rural areas which can benefit from particular forms of economic or other assistance. These boundaries seek to identify the areas which exhibit distinctive problems, yet this remains far from simple because even the definition of rural areas remains problematic in Britain. Monitoring the continuing appropriateness of existing policy boundaries by compiling up-to-date data for these areas is made more difficult by the fact that these non-standard areas are not recognized by the units used for reporting relevant statistics. This technical problem is explored through the example of compiling Population Census data for Less Favoured Areas: these upland area definitions provide a stern test of the possible benefits from a geographic information system (GIS) approach. The results from this experiment raise again key questions in the definitions of rural and upland areas, and how these areas should be represented statistically.